Pengaruh Tax Avoidance, Leverage, Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Dengan Transparansi Perusahaan Sebagai Variabel Moderating(Studi Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia (Bei) Tahun 2016-2018) - Silvia Ramadhiani; Santi Rahma Dewi (International Journal on Human-Computing Studies, 2021)
This study aims to determine the effect of tax avoidance, leverage, and managerial ownership on firm value with company transparency as a moderating variable. Tax Avoidance is measured by CASH ETR, Leverage is measured by DER, Managerial ownership is obtained from annual reports on mining companies that are listed on the IDX. This research was conducted on mining companies that have been listed on the Indonesia Stock Exchange (BEI) in 2016-2018.This research was conducted using quantitative methods, using MRA data analysis. The results of this study indicate that (1) Tax Avoidance has an effect on Firm Value, (2) Laverage has an effect on Firm Value, (3) Managerial Ownership has an effect on Firm Value, (4) Transparency is able to moderate the effect of Tax Avoidance on Firm Value, (5) Transparency is able to moderate the effect of leverage on firm value, (6) transparency is able to moderate the effect of managerial ownership on firm value.